Kenneth Warren and the Great Neglected Diseases of Mankind Programme : The Transformation of Geographical Medicine in the US and Beyond - Keating, Conrad (Springer International Publishing : Imprint: Springer, 2017)
Kenneth Warren was a powerful figure in twentieth century medicine whose work transformed public health policy and tropical medicine, and who left a profound legacy in global health thinking. A prolific writer and researcher, Warren was respected for his scientific research, winning awards and accolades, while his later role as activist, agitator, innovator and connoisseur of science brought him international recognition. His career in medicine is remembered for three enduring achievements: · His efforts to introduce modern biomedical science to the study of infectious diseases in the developing world · The proselytising energy he brought to the ethical challenge of how to provide the most cost-effective health care to the world's poorest people · His tenure as Director of Health Sciences at the Rockefeller Foundation, during which time he inaugurated the Great Neglected Diseases of Mankind Programme Told through personal interviews with both Warren's supporters and detractors, the story of Warren's career, inexorably interwoven with the GND programme, is a compelling narrative that has not only enduring implications for current medical research, funding and healthcare across the globe, but also a long-standing legacy for the future ways in which we combat disease in the developing world. .
Keywords: Popular works.; Vaccines.; Infectious diseases.; Medicine.; Health.; elektronické knihy; electronic books